DISTRIBUTION OF BLOOD TYPE AND Rh FACTOR AMONG BLOOD DONORS OF LAHORE - Saeed, Muhammad; Hussain, Shahida; Arif, Mizna (Pakistan Armed Forces Medical Journal, 2016)
Objective: Present study was designed to provide baseline data about distribution frequency of blood type and Rh factor among blood donors of Lahore.Study Design: Cross sectional study.Place and Duration of Study: Department of Transfusion Medicine Jinnah Hospital Lahore from January 2012 to December 2014.Patients and Methods: A retrospective data of ABO/Rh typing done by manual hema-agglutination techniques of total 17994 blood samples were collected by non probability consecutive sampling technique and analyzed for ABO/Rh typing. Demographic characteristics age and gender were noted and cross tabulation for gender and ABO/Rh typing was done. Chi-square test was used to assess any statistical association.Results: Out of total 17994 donors, 90.83% (16344) were Rh positive and 9.16% (1650) were Rh negative. Blood group “B” was found to be most prevalent, with the frequency of 6127 (34.05%), followed by “O” 5980 (33.2%), and “A” 4210 (23.39%) respectively. “AB” group was least common with a frequency of 1677 (9.31 %). 23.9% of male donors were of blood group type “A”, 34.5% were type “B”, 33.3% were type “O” and 8.3% had “AB”. 6.2% of female donor were of blood group type “A”, 18.6% were of type “B”, 32.0% were having type “O” and 43.2% had “AB”. (p=.000).Conclusion: We conclude that the over all frequency distribution of ABO blood groups in study population of Lahore is “B”> “O”> “A”> “AB”. Blood group “B” was most prevalent and AB the least prevalent. Rh positive phenotype is predominant (90.8%) with distribution of “B”+ve >, “o”+ve> “A”+ve > “AB”+ve. In group of Rh negative phenotype (9.2%) “o”-ve > “B”-ve > “A”-ve> “AB”-ve.